Clinical impact of intraoperative CCEP monitoring in evaluating the dorsal language white matter pathway. Issue 4 (23rd January 2017) - Yamao, Yukihiro; Suzuki, Kengo; Kunieda, Takeharu; Matsumoto, Riki; Arakawa, Yoshiki; Nakae, Takuro; Nishida, Sei; Inano, Rika; Shibata, Sumiya; Shimotake, Akihiro; Kikuchi, Takayuki; Sawamoto, Nobukatsu; et al.
Abstract: In order to preserve postoperative language function, we recently proposed a new intraoperative method to monitor the integrity of the dorsal language pathway (arcuate fasciculus; AF) using cortico–cortical evoked potentials (CCEPs). Based on further investigations (20 patients, 21 CCEP investigations), including patients who were not suitable for awake surgery (five CCEP investigations) or those without preoperative neuroimaging data (eight CCEP investigations including four with untraceable tractography due to brain edema), we attempted to clarify the clinical impact of this new intraoperative method. We monitored the integrity of AF by stimulating the anterior perisylvian language area (AL) by recording CCEPs from the posterior perisylvian language area (PL) consecutively during both general anesthesia and awake condition. After tumor resection, single‐pulse electrical stimuli were also applied to the floor of the removal cavity to record subcortico‐cortical evoked potentials (SCEPs) at AL and PL in 12 patients (12 SCEP investigations). We demonstrated that (1) intraoperative dorsal language network monitoring was feasible even when patients were not suitable for awake surgery or without preoperative neuroimaging studies, (2) CCEP is a dynamic marker of functional connectivity or integrity of AF, and CCEP N1 amplitude could even become larger after reduction of brain edema, (3) a 50% CCEP N1 amplitude decline might be a cut‐off value to prevent permanent language dysfunction due to impairment of AF, (4) a correspondence (<2.0 ms difference) of N1 onset latencies between CCEP and the sum of SCEPs indicates close proximity of the subcortical stimulus site to AF (<3.0 mm). Hum Brain Mapp 38:1977–1991, 2017 . ©2017 Wiley Periodicals, Inc.